Correlation of Cancer Caregiver's Burden, Stress, and Their Quality of Life - Fellia, Theodora; Sarafis, Pavlos; Bouletis, Axilleas; Tzenetidis, Vasileios; Papathanasiou, Iokasti; Apostolidi, Theodora-Paisia; Gkena, Niki; Nikolentzos, Athanasios; Patsopoulou, Anna; Malliarou, Maria (My University, 2023)
The purpose of this study is to examine the stress levels felt by family caregivers. The main objectives of this study are (a) the cross-examination of family caregiver's burden, (b) caregiver's stress levels and its impact on burden feeling, also (c) the effect of caregiving on caregiver's quality of life.
Keywords: Cancer; Caregiver burden; Parenteral nutrition; Quality of life